Chronic meningococcemia in a vertically HIV-infected adolescent - Rita S.B. Cardona (IDCases, 2020)
Chronic meningococcemia is a rare manifestation of meningococcal disease, characterized by a period of more than one week of intermittent or continuous fever, arthralgia and skin lesions without meningitis. It can occur both in previously healthy and immunocompromised patients. The gold standard for the diagnosis is culture isolation of Neisseria meningitidis in sterile material. We describe a case of a vertically HIV-infected adolescent with chronic meningococcal disease.